Features of ‘Nenglish’, an Emerging Variety of English - Koirala, Ishwar (Journal of Business and Social Sciences, 2021)
English has gained a high value in Nepalese societies. The craze of English Medium Instruction at schools, use of English in government and private offices and adoption of it by Nepalese speaker has shown that English has slowly become our property, our language. As a result we are on the way to develop ‘our English’ i.e. Nenglish or Nepanglish.  This paper excavates and explains the features of Nepali English that is used commonly in Nepal. This article is mainly a desk research which also includes researcher’s observation of the English phenomena in the town. The findings show that Nepali English is on the way to being a special variety of English and has several features such as being influenced by ‘Hinglish’; utilizing American lexicon; adopting words from Sanskrit language; including special modification and coinage; Nepaliness in pronouncing and adding tag questions etc.